Impact of Voiding and Incontinence Symptoms on Health-Related Life Quality in Serbian Male Population - Babic, Uros; Santric-Milicevic, Milena; Terzic, Zorica; Argirovic, Aleksandar; Kojic, Dejan; Stjepanovic, Mihailo; Lazovic, Dejan; Bjegovic-Mikanovic, Vesna; Vukotic, Vinka (Urology Journal, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> Introduction: Impact of lower urinary tract symptoms on health-related quality of life in Serbian population considering socio-demographic characteristics, habits and health status. Methods: The study was conducted in the Primary Healthcare Center Novi Beograd. The study included 1424 male participants, aged 40 and above. The quality of life was measured by using the SF-36 questionnaire, while voiding and incontinence symptoms were measured by using the International Continence Society Male Short Form (ICS male SF) questionnaire. Results: Voiding and incontinence symptoms significantly correlate with all dimensions of life quality. Voiding and incontinence symptoms have a higher influence on some dimensions like general health, social functioning, physical functioning and body pain while they have a low but still statistically significant impact on physical, emotional and mental health. After adjusting for age and education, voiding and incontinence symptoms had a similar influence on life quality but lower than before. In a multivariate model, life threatening morbidities and income had an influence on life quality lower than voiding and incontinence symptoms. Conclusion: Voiding and incontinence symptoms affect life quality dimensions differently. Incontinence symptoms have impact on life quality higher than voiding symptoms. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->